Heat Flow and Near‐Seafloor Magnetic Anomalies Highlight Hydrothermal Circulation at Brothers Volcano Caldera, Southern Kermadec Arc, New Zealand - F. Caratori Tontini; M. A. Tivey; C. E. J. deRonde; S. E. Humphris (Geophysical Research Letters)
Abstract Brothers volcano is the most hydrothermally active volcano along the Kermadec arc, with distinct hydrothermal fields located on the caldera walls and on the postcollapse volcanic cones. These sites display very different styles of hydrothermal activity in terms of temperature, gas content, fluid chemistry, and associated mineralization. Here we show the results of a systematic heat flow survey integrated with near‐seafloor magnetic data acquired using remotely operated vehicles and autonomous underwater vehicles. Large‐scale circulation is structurally controlled, with a deep (~1‐ to 2‐km depth) central recharge through the caldera floor and lateral discharge along the caldera walls and at the summits of the postcollapse cones. Shallow (~ 0.1‐0.2 km depth) circulation is characterized by small‐scale recharge zones located at a distance of ~ 0.1–0.2 km from the active vent sites.